Fine-mapping of the bitterness locus in almond - Ricciardi F.; del Cueto J.; Lotti C.; Pavan S.; Ricciardi L.; Dhingra A.; Dicenta F.; Moller B.L.; Sánchez-Pérez R. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
During domestication, almond kernels have been selected for low content of amygdalin, a cyanogenic glucoside responsible for bitterness. The taste of the almond kernel is under monogenic control, with the dominant sweet kernel (Sk) allele associated to sweetness and the recessive sk allele associated to bitterness. Since most of the cultivated almonds are heterozygous, new bitter almond seedlings are usually obtained during breeding programs and it is valuable to develop molecular markers enabling assisted selection. Although its biochemical function remains unidentified, the SK gene has been localised on linkage group five (G5) in the almond genetic linkage map obtained from the cross between the two heterozygous genotypes ‘R1000’ and ‘Desmayo Largueta’ (RxD). We report here the identification of several SNPs over a 3.7 Mb peach (Prunus persica L.) physical region, which is synthenic to the one containing the Sk locus in almond. Some of them were converted into cleaved amplified polymorphic DNA (CAPS) markers suitable for assisted selection. Further studies are in progress aiming to the functional characterization of candidate genes for controlling the phenotype.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)